2013
DOI: 10.4172/2155-9880.1000238
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplement-5 with a Combination of Proteasome Inhibitors (Resveratrol, Quercetin, δ-Tocotrienol) Modulate Age-Associated Biomarkers and Cardiovascular Lipid Parameters in Human Subjects

Abstract: Background Age-associated altered redox imbalances and dysregulated immune function, contribute to the development of a variety of age associated diseases. Inflammatory markers and lipid profiles are useful prognostic indicators of a variety of age-associated and cardiovascular diseases. We have previously studied the impact of several proteasome inhibitors on several markers of inflammation and lipid profiles in vitro, in vivo, in cell lines, animal models, and in human subjects. The current study represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…The correlation between plasma levels of several pro-inflammatory and anti-inflammatory cytokines affected by δ-tocotrienol treatment has been reported in our recent publications [4,5,37]. Most of the cytokines (eight out of eleven) were down-regulated in a dosedependent manner by δ-tocotrienol treatment, except adiponectin, tumor growth factor β1 and leptin (Table 6).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The correlation between plasma levels of several pro-inflammatory and anti-inflammatory cytokines affected by δ-tocotrienol treatment has been reported in our recent publications [4,5,37]. Most of the cytokines (eight out of eleven) were down-regulated in a dosedependent manner by δ-tocotrienol treatment, except adiponectin, tumor growth factor β1 and leptin (Table 6).…”
Section: Discussionsupporting
confidence: 62%
“…The phenomena of bioconversion of tocotrienols to tocopherols have been discussed in earlier publications [4][5][6]29]. It was reported that failure of large doses of palm TRF and rice bran TRF25 to lower lipid parameters in hypercholesterolemic subjects maybe due to their conversion to tocopherols, because the plasma concentrations of tocopherols were 2-to 4-fold higher than tocotrienols as compared to placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] RES has received much attention in recent years because of its various health functions and its potential for use in medicinal applications. 4,5) Many studies have demonstrated that RES has significant pharmacological activity 6) and potential to be a chemopreventive and therapeutic agent for cancers, [7][8][9] Alzheimer's disease, 10) cardiovascular disease, 11) hyperlipidemia, 12) ischemia disease and other diseases. 13) Recently, RES has seen widespread use as a food ingredient and nutraceutical supplement in bread, cake and beverage products.…”
mentioning
confidence: 99%